Project management (B.Sc [IT] T.Y. 6th semester) - Gaikwad Rajesh L., Joshi Brijesh Y. and others (Vipul prakashan,Mumbai)
Computer
Sent to BSc (IT) Dept. dt.25/1/08
ENGLISH
Keywords: Project management (B.Sc [IT] T.Y. 6th semester); Computer; Computer